EVALUATION OF THE USE OF TEACHING MATERIALS IN SITUATION-BASED LEARNING IN THE CITY OF GOMA. CASE STUDY OF THE DELA SCHOOLS IN THE KARISIMBI SUB-DIVISION - WIMANA SAMSON Toussaint, (IJRDO- Journal of Educational Research, 2024)
The aim of this research was to describe the effect of applying the Situation-Based Approach (SAP) approach in teaching. This description took into account the verification of teaching materials in schools. Using descriptive methods, questionnaires, observation, interviews and documentaries, data from the analysis was collected from 89 teachers and 266 pupils in the Karisimbi 1 Sub-division. The results of the analysis are presented as follows:- Firstly, APS develops critical thinking, facilitates self-learning and the construction of knowledge and skills,- Secondly, with regard to MADI's contribution to APS, the analysis of the Kolmogorov-Sminirov Normality Test demonstrates the existence of a gap in the presence of MADI within the schools, justified by the fact that the data (MADI) are not normally distributed (P-value being 0.000 and 0.001 <0.05).